A surveillance model for sexually transmitted infections in India - Partha Haldar; Guy Morineau; Anjana Das; Sanjay Mehendale (Wolters Kluwer Medknow Publications, 2015)
The strategy for prevention and control of sexually transmitted infections (STIs) in India is based on syndromic case management delivered through designated STI/reproductive tract infection (RTI) centers (DSRCs) situated in medical colleges, district hospitals, and STI-clinics of targeted interventions programs. Laboratory tests for enhanced syndromic management are available at some sites. To ensure country-level planning and effective local implementation of STI services, reliable and consistent epidemiologic information is required on the distribution of STI cases, rate and trends of newly acquired infections, and STI prevalence in specific population groups. The present STI management information system is inadequate to meet these requirements because it is based on syndromic data and limited laboratory investigations on STIs reported passively by DSRCs and laboratories. Geographically representative information on the etiology of STI syndromes and antimicrobial susceptibility of STI pathogens although essential for optimizing available treatment options, is deficient. Surveillance must provide high quality information on: (a) prevalence of STIs such as syphilis, trichomoniasis, gonorrhea, and chlamydia among high-risk groups; syphilis in the general population and pregnant antenatal women; (b) demographic characteristics such as age, sex, new/recurrent episode, and type of syndromically diagnosed STI cases; (c) proportion of acute infections such as urethral discharge (UD) in men and nonherpetic genital ulcer disease (GUD) in men and women; (d) etiology of STI syndromes; and (e) gonococcal antimicrobial susceptibility. We describe here a framework for an STI sentinel surveillance system in India, building on the existing STI reporting systems and infrastructure, an overview of the components of the proposed surveillance system, and operational challenges in its implementation.